AS A PEDAGOGICAL PROBLEM OF IMPROVING THE FUNDAMENTALS OF DIGITAL TECHNOLOGY OF FORMING COMPETENCES OF PRIMARY CLASS STUDENTS IN THE SCIENCE OF PHYSICAL EDUCATION - Sayfullayev Azizbek Amrillo o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the issue of effective teaching of primary school students, the choice of methods capable of achieving this goal. It is proposed to combine the classical methods of teaching and conducting classes and new, didactic methods, taking into account the individual learning abilities of each primary school student. Particular attention is paid to the grouping method. The article is intended for teachers working in the direction of "Primary education" and students studying in the direction of "Primary education".